Equity - Worthington, Sarah (Oxford University Press, 2003)
Equity is traditionally, if imprecisely, regarded as the 'conscience' of the law. Despite this, there is no English textbook on general equitable principles. The emphasis has instead been on providing detailed and sophisticated descriptions of the law of trusts. The role of Equity, and its relationship with the Common Law rules of contract, restitution, and property have been relatively ignored, yet they present issues on which opinion is sharply divided. Sarah Worthington's new book provides an outline of the basic principles of equity, illustrated principally by contemporary examples of its operation. It considers Equity's role in creating different rights and obligations, different remedies, and different procedures from those provided by the common law itself. In exploring these areas, the overriding aim is to delimit equity's modern role and it's present relationship with other areas of the law. Most importantly, this book exposes the possibilities, and the need, for coherent substantive integration of common law and equity